2002
DOI: 10.1038/ng876
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence that oxidative derivatives of retinoic acid are not involved in retinoid signaling during mouse development

Abstract: ).Retinoic acid, the active derivative of vitamin A (retinol), is a hormonal signaling molecule that acts in developing and adult tissues 1 . The Cyp26a1 (cytochrome p450, 26) protein metabolizes retinoic acid into more polar hydroxylated and oxidized derivatives 2,3 . Whether some of these derivatives are biologically active metabolites has been debated 4,5 . Cyp26a1 -/-mouse fetuses have lethal morphogenetic phenotypes mimicking those generated by excess retinoic acid administration, indicating that human CY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
217
1
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(224 citation statements)
references
References 20 publications
3
217
1
3
Order By: Relevance
“…3E,F). This demonstrates that, as for other phenotypes observed in cyp26a1-mutant fish and mice (Emoto et al, 2005;Niederreither et al, 2002), the posteriorized hindbrain phenotype caused by blocking all Cyp26 activity is due to the accumulation of excess RA and not to the absence of bioactive Cyp26-generated RA derivatives. Although such derivatives have been observed to have significant retinoidal effects in cells and in embryos, and have been postulated to have functions in vivo (Idres et al, 2002;Pijnappel et al, 1993), we see no evidence for their having a role in hindbrain patterning.…”
Section: Research Articlementioning
confidence: 83%
See 1 more Smart Citation
“…3E,F). This demonstrates that, as for other phenotypes observed in cyp26a1-mutant fish and mice (Emoto et al, 2005;Niederreither et al, 2002), the posteriorized hindbrain phenotype caused by blocking all Cyp26 activity is due to the accumulation of excess RA and not to the absence of bioactive Cyp26-generated RA derivatives. Although such derivatives have been observed to have significant retinoidal effects in cells and in embryos, and have been postulated to have functions in vivo (Idres et al, 2002;Pijnappel et al, 1993), we see no evidence for their having a role in hindbrain patterning.…”
Section: Research Articlementioning
confidence: 83%
“…The posterior limit of cyp26a1 expression lies in the anterior hindbrain (Dobbs-McAuliffe et al, 2004;Kudoh et al, 2002;Sirbu et al, 2005), whereas both cyp26b1 and cyp26c1 mark, sequentially, the r4-r5 and r6-r7 boundaries. However, it is important to notice that cyp26a1 is also expressed in the anterior trunk mesoderm near the RA source, where it probably functions to reduce global RA levels (Emoto et al, 2005;Niederreither et al, 2002). We propose that the severe posteriorization of Cyp26-depleted embryos results from the combined effects of depleting segment-restricted Cyp26 activity within the hindbrain and increasing global RA levels due to the loss of Cyp26a1 activity in the anterior trunk mesoderm (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model with mutated RALDH2 and CYP26, the hydroxylated derivates of CYP26 were shown to be biologically inactive (Niederreither et al, 2002). We have recently shown that manipulation of RA concentrations has profound effects on differentiation status ex vivo (Chang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A member of the cytochrome P450 family, CYP26A1, has recently been identified as a major RA-catabolizing enzyme, which converts RA to biologically inactive hydroxylated retinoid derivatives (Niederreither et al, 2002). CYP26A1 has been shown to be upregulated in human familial adenomatous polyposis adenomas, sporadic colon cancers and primary ovarian cancer (Downie et al, 2005;Shelton et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…CYP26A1 has been reported to be the principal enzyme responsible for the catabolism of at-RA to the inactive polar metabolites, 4-hydroxy-RA (4-OH-RA) , 4-oxo-RA, and 18-OH-RA [6][7][8]. Although some studies have suggested that 4-OH-RA and 4-oxo-RA have biological activity [9][10][11], other recent studies have suggested that these metabolites are principally inactive breakdown products of at-RA [1,5]. Cyp26a1 null mice die during mid-late gestation [7,12] .…”
Section: Introductionmentioning
confidence: 99%